STRATEGI PENGELOLAAN WISATA ALAM BERBASISKAN MASYARAKAT DI TAMAN NASIONAL BUKIT TIGAPULUH DESA RANTAU LANGSATKECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU PROVINSI RIAU - Ningsih, Rifda; Yoza, Defri; Sribudiani, Evi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The Bukit Tiga Puluh National Park(TNBT) set in 2002withthe aim ofprotecting theecologicalprocessesthat supportlife, preserve theflora, faunaandecosystemsthat existinthe national parkas well asfor the development ofscience, education, research, support activities ofcultivation, as well astourismin order to utilize natural resourcesin a sustainable manner.The growing popularity ofecotourismin societytodayandthe tendency ofthe increasing scarcity of naturalauthenticity potential, thenefforts to useTNBT functionasecotourismdestinationshouldbe realizedwithout further delay.This activity is expectedto bringpositiveimplicationson the economy ofthe community, as well as foster a culture oftourism awarenessandpro-conservation as a tourism assetandsustainer of life.The research was conductedinNovember -December 2014onEcotourismCommunity Careof RantauSalo(MPERS), in theRantauLangsatVillage, Thisstudyusedsurveymethodsand field observations. Datafrom the studywere analyzeddescriptively.Based onresults of theresearch, MPERShave a wide choiceof alternativestrategies thatdirectattention tothe strengths, weaknesses, opportunitiesandthreats.Furthermore, the right strategytobe appliedin the development ofMPERStodayisa functionalstrategy.Functional strategyis the approach takenfromeachfunctional(HR functions, management, etc.), whichcombines a varietyof activitiesandcompetenciesofeachfunctiontoimprove performance. Keywords: Ecotourism, MPERS, TNBT